Comparative Genomics, Evolutionary and Gene Regulatory Regions Analysis of Casein Gene Family in Bubalus bubalis - Rehman, Saif ur; Feng, Tong; Wu, Siwen; Luo, Xier; Lei, An; Luobu, Basang; Hassan, Faiz-ul; Liu, Qingyou (Frontiers in Genetics, 2021)
Buffalo is a luxurious genetic resource with multiple utilities (as a dairy, draft, and meat animal) and economic significance in the tropical and subtropical regions of the globe. The excellent potential to survive and perform on marginal resources makes buffalo an important source for nutritious products, particularly milk and meat. This study was aimed to investigate the evolutionary relationship, physiochemical properties, and comparative genomic analysis of the casein gene family (CSN1S1, CSN2, CSN1S2, and CSN3) in river and swamp buffalo. Phylogenetic, gene structure, motif, and conserved domain analysis revealed the evolutionarily conserved nature of the casein genes in buffalo and other closely related species. Results indicated that casein proteins were unstable, hydrophilic, and thermostable, although αs1-CN, β-CN, and κ-CN exhibited acidic properties except for αs2-CN, which behaved slightly basic. Comparative analysis of amino acid sequences revealed greater variation in the river buffalo breeds than the swamp buffalo indicating the possible role of these variations in the regulation of milk traits in buffalo. Furthermore, we identified lower transcription activators STATs and higher repressor site YY1 distribution in swamp buffalo, revealing its association with lower expression of casein genes that might subsequently affect milk production. The role of the main motifs in controlling the expression of casein genes necessitates the need for functional studies to evaluate the effect of these elements on the regulation of casein gene function in buffalo.